(untitled) (International journal of artificial intelligence, 2025)
The article reveals the basic concepts of the modeling method in social psychology, the construction of a structural-functional model for the prevention of deviant behavior of adolescents in specialized boarding schools. Great importance is attached to corrective work with minors with certain deviations in behavior.